Supplementary analysis of the 2003 survey of FCHVs in the 17 core program districts. (2004)
EXECUTIVE SUMMARY: Introduction The Nepal Family Health Program (NFHP), funded by USAID-Nepal, aims to improve access to and the quality and quantity of maternal and child health services that are available through government health facilities in 17 Core Program Districts (CPDs) in Nepal. An annual survey of 100 randomly selected Female Community Health Volunteers (FCHVs) in each of the CDPs is an important part of the external monitoring component of the NFHP and is unique among similar efforts in Nepal in its exclusive and in-depth focus on FCHVs and their performance. The principle objective of this survey is to provide information regarding FCHV characteristics in order to monitor the progress of the NFHP. Initial analyses of the FCHV surveys of 2002 and 2003 have been conducted and are reported elsewhere. This document describes the results of a supplementary analysis of the 2003 FCHV survey. Major findings and conclusions ARI Case Management 1. FCHVs diagnose 40 percent of the ARI cases they see as pneumonia. There are two groups of FCHVs with respect to this variable: one that diagnoses approximately 50 percent of ARI cases as pneumonia, and another at approximately 10 percent. Treatment FCHVs (TFs) diagnose a higher percentage (43 percent) of the ARI cases they see as pneumonia than do Referral FCHVs (RFs; 33 percent). 2. FCHVs see an average of 3.2 children per month with ARI. Estimates for this indicator across districts range broadly from 0.5 in Banke to 7.7 in Morang. Despite the breadth of this range, districts are distributed normally in one dispersed group. FCHVs, however, form two groups: one that is completely inactive (18 percent of FCHVs) and another that demonstrates low-to-moderate ARICM activity levels. Among FCHVs who see children with ARI, FCHVs whose registers served as the sole data source see more cases of ARI per month (5.1) than FCHVs who provided information through recall (3.4). 3. Treatment FCHVs (TFs) manage more than three times as many ARI cases than Referral FCHVs (4.9 versus 1.5 cases per month). 36 percent (206/576) of surveyed RFs are completely inactive with regards to ARICM as compared to only 5 percent (54/990) of surveyed TFs. TFs form a single group of FCHVs performing ARICM at a moderately active level. RFs are best conceptualized as consisting of two groups of FCHVs: one that is inactive in ARICM and another that has generally low levels of activity. 4. Six percent of children diagnosed with pneumonia by TFs do not receive cotrim from TFs due to lack of supplies. 77 percent of TFs have no "unable to treat" cases; the remaining 23 percent of TFs are unable to treat 21 percent of their patients with pneumonia due to lack of cotrim. District-level estimates range from 1.7 percent in Morang to 13.5 percent in Rasuwa. Districts with high levels of "unable to treat" cases owe this distinction to a relatively small number of TFs who have a high proportion of "unable to treat" cases. 5. Survey-based estimates measuring levels of ARI case management by FCHVs are highly correlated with NFHP administrative estimates. The two estimates are not independent, as they both rely heavily on FCHV ARI Registers as a data source. The observed correlation suggests that the data collected by the NFHP are an accurate representation of FCHVs' recorded and reported activities in pneumonia case management. Safe Motherhood 6. FCHVs counsel an average of 25 (median of 18) pregnant women (PW) per year. While almost all FCHVs (99.8 percent) report that they counsel PW, the majority counsel relatively few. Estimates of this variable at the district-level range from 5 PW per year in Rasuwa to 44 PW per year in Morang. Districts appear to be divided into two groups-a "low counseling" group of districts centered at an aver age of slightly more than 12 PW counseled per year and another group of districts centered at approximately thirty PW counseled per year.7. 82 percent of all PW are counseled at least once by FCHVs. Estimates of this variable at district-level range from 36 percent in Nawalparasi to 155 percent in Kailali. One or more of the assumptions that are required to calculate this indicator, including the use of expected pregnancies as the denominator, may have led to overestimates. 8. FCHVs refer an average of 4.9 PW, 3.1 post-partum women (PPW), and 2.9 newborns with complications per year (median of 2.0, 0, and 0, respectively). With regards to these variables, FCHVs can be thought of as forming two groups-one group that never makes referrals of any of the three client groups (25 percent of all FCHVs), and a second that makes a moderate number of referrals. Distributions of these variables at the district-level are unimodal, normally distributed, and broad-for example, FCHVs in Rautahat and Dhanusha refer more than ten times as many clients with complications than FCHVs in Rasuwa and Bardia. 9. FCHVs refer 18.3 percent of the PW whom they counsel. 36 percent of FCHVs never refer pregnant women. FCHVs can be clearly divided into two groups-one group that never refers, and another broadly defined group that does make referrals. Districts also form two groups- "high-referral districts" where FCHVs refer 25 percent or more of the PW they counsel, and "lowreferral districts" where FCHVs refer 10-20 percent of the PW they counsel. 10. 15.5 percent of all PW, 9.9 percent of all PPW, and 9.2 percent of all newborns are referred by an FCHV. Referral rates among these three client groups follow similar patterns across districts. Two groups of districts emerge from visual inspections of the distributions-highreferral districts (Bajura, Rautahat, Parsa, Kailali, Dhanusha and Banke for newborns, PW and PPW; Bara and Sunsari for PW only) and low-referral districts (remaining districts). General 11. There are no discernible patterns of findings among districts. The wide variety of inputs and factors that impact upon pneumonia case management and safe motherhood activities in the surveyed districts includes the presence and timing of project-related activity (e.g., NFHP, the Nepal Safe Motherhood Project, and projects conducted by other national and international NGOs), geographical issues, and the conflict. The mixture of these inputs and factors do not permit broad conclusions to be reached regarding their contribution to differences in indicators that are observed at the district-level. 12. Notable percentages of FCHVs are inactive. Several analyses disclosed large groups of FCHVs who are completely inactive with regards to particular activities. 18 percent of respondents do not see children with ARI, 25 percent are completely inactive in referral of PW / PPW / newborns, and 7 percent do not perform activities in either area.